Understanding area-based community empowerment initiatives as events in systems and the implications for evaluating their potential to affect health inequalities. (13th November 2015) - Halliday, Emma; Orton, Lois; Egan, Matt; Lewis, Sue; Powell, Katie; Townsend, Anne; Tyrrell, Rachel; Whitehead, Margaret; Popay, Jennie
Abstract: Background: Evaluation of community empowerment initiatives for their effects on health inequalities presents a paradox to researchers. By definition, such initiatives aim to empower people to influence decisions that affect their lives. However, once empowered, people might not necessarily take the decisions that the originators of the intervention desired. The inability to control the implementation of an intervention goes against all the basic principles of intervention trials. We studied a community empowerment initiative, using a systems approach, to see whether any ensuing diversity of implementation could be used as an advantage rather than be a problem for an evaluation design. Methods: We conducted qualitative in-depth case studies in ten intervention neighbourhoods in England, including a total of 150 resident interviews and ethnographic observation, interviews with the national organisations involved, and a review of plans from 30 intervention sites. Data were coded in NVivo (version 10) in a pre-defined thematic framework. Narrative memos were developed and compared and contrasted across sites. Findings: The initiative's overarching objective was to increase confidence and skills to enable residents to identify priorities and take action in their neighbourhoods. Our fieldwork found that the core objective was pursued in different ways: building connections across people living or working in the neighbourhood, promoting social participation, improving or so-called lifting an area's external reputation, achieving material improvements (eg, parks), and addressing debt or unemployment. Diversity in starting points of local area systems also contributed to divergence in the aspirations that residents identified, the actions being taken to achieve them, and the change in processes that ensued. Interpretation: Understanding interventions as events in systems offers an approach that shifts the focus of assessment from what works to what happens when an intervention interacts with multiple local systems. This approach reveals how and why the intervention adapts over time as communities develop new capacities and learn from early implementation. The resulting diversity created across different sites can be exploited for evaluation purposes—for example, by creating internal comparators. This diversity offers potential for understanding how such interventions unfold over time and the differential health and social effects that might ensue. Funding: This paper presents independent research funded by the National Institute for Health Research (NIHR) School for Public Health Research.